Integrated Planning for Sustainable Clean Water and Sanitation at Mulawarman University - Fahrizal Adnan; Febrina Zulya; Searphin Nugroho; Rahmahtriananda Faradilla; Aulia Fauziyah Luayi; Rizqi Nadhirawati; Budi Nining Widiarti; Ibrahim Ibrahim (International Journal of Engineering, Science and Information Technology, 2026)
Clean water and sanitation are essential components of a healthy, safe, and sustainable campus environment. At Mulawarman University, increasing numbers of students, lecturers, staff, and other academic community members require adequate water supply and sanitation infrastructure to support educational, administrative, and daily activities. This study aims to develop a long-term plan for clean water provision and sanitation facilities based on projected population growth through 2048. The methodology includes population projection analysis, estimation of clean water demand, assessment of sanitation facility requirements, and planning for solid and liquid waste management. The results indicate that demand for clean water and sanitation infrastructure will increase consistently with the growth of the university population. At the end of the sixth planning period in 2048, the projected served population reaches 64,458 people. This population requires a clean water production capacity of 966.88 m³/day to meet projected demand. Solid-waste management requirements include ten temporary waste-storage facilities (TPS), three dump-truck fleets, and one integrated waste-treatment facility (TPST) with an estimated required area of 1,129.38 m². Meanwhile, wastewater management must accommodate a potential black-water discharge of 96.69 m³/day and grey-water discharge of 676.81 m³/day. Based on these projections, the study recommends developing an integrated clean-water distribution network, improving solid-waste collection and treatment facilities, and establishing an integrated wastewater-management system capable of accommodating future demand. The proposed planning framework is expected to support Mulawarman University in improving environmental quality, strengthening campus sanitation services, and achieving more sustainable infrastructure development. Furthermore, the findings provide a quantitative basis for phased infrastructure investment and long-term campus environmental management through 2048